CaMKIIβ in Neuronal Development and Plasticity: An Emerging Candidate in Brain Diseases - Nicole, Olivier; Pacary, Emilie (International journal of molecular sciences, 2020)
The calcium/calmodulin-dependent protein kinase II (CaMKII) is a ubiquitous and central player in Ca2+ signaling that is best known for its functions in the brain. In particular, the α isoform of CaMKII has been the subject of intense research and it has been established as a central regulator of neuronal plasticity. In contrast, little attention has been paid to CaMKIIβ, the other predominant brain isoform that interacts directly with the actin cytoskeleton, and the functions of CaMKIIβ in this organ remain largely unexplored. However, recently, the perturbation of CaMKIIβ expression has been associated with multiple neuropsychiatric and neurodevelopmental diseases, highlighting CAMK2B as a gene of interest. Herein, after highlighting the main structural and expression differences between the α and β isoforms, we will review the specific functions of CaMKIIβ, as described so far, in neuronal development and plasticity, as well as its potential implication in brain diseases.